(untitled) (Global Journal of Management and Business Research, 2020)
With the increasingly complicated, sensitive and perilous Sino-US relations amid the COVID-19 pandemic, it requires a historical, comprehensive and systematic thinking to deal with the increasing risk of Sino-US cold war. This paper conducted some preliminary and systematic analysis into the crux and the approaches to resolve the tensions. At such a critical juncture of the Sino-US relations, the crux of problems is manifested in the following aspects: coronavirusrelated stigma; all-round trade disputes; politicization of trade; complication of politics; directly targeted strategy; deteriorating corporate and social base; ideological radicalization. The principal contradictions are those incurred by different national strategic interests. The US is worried about being replaced by China and the impact of China’s "nationwide system" on the current international system. On the other hand, China is worried about the US’ interference into its internal affairs, system building and national reunification, as well as the US’ efforts to contain China’s development.